Hadjibalassi, Maria - (:unkn) unknown (My University, 2026)
Maria Hadjibalassi is a lecturer in Department of Nursing. She has a postgraduate degree in Critical Care Nursing from Middlesex University (UK), bachelor in Nursing Education from Anglia Polytechnic University (UK) and Diploma in Nursing and also a post-basic Diploma in Intensive Care from School of Nursing of Cyprus. Her research interests include issues such as change in care provision systems aiming to improvement of care provided, competencies of critical care nurses and competency based education and others.